"I'm Trying To Be the Safety Net": Family Protection of Patients With Moderate-To-Severe TBI During the Hospital Stay. (October 2017) - Oyesanya, Tolu O.; Bowers, Barbara
Research has shown that during hospital stay, family caregivers of patients with traumatic brain injury (TBI) perceive that their role is to protect the patient; however, research on this topic is limited. The purpose of this article is to describe family caregivers' experience of protecting patients with TBI during the hospital stay. Grounded theory was used to conduct 24 interviews with 16 family caregivers. Findings showed family caregivers worked to protect the patient's physical and emotional safety, using the following strategies: (a) influencing the selection of staff, (b) breaking the patient's bad habits, (c) anticipating how to orchestrate the home environment; (d) connecting on an emotional level, (e) managing visitors, and (f) connecting on an emtoional level. The findings have practice implications for educating interdisciplinary health care providers about the experience of family caregivers and for developing an adversarial alliance between health care providers and family caregivers during the hospital stay to improve support provided to them.